SIM-RS Success Factors Based on DeLone and McLean Theory at Hermina OPI Jakabaring Hospital - Hikma, Yusnita Ayu; Yuliaty, Farida (Jurnal Indonesia Sosial Sains, 2024)
The information technology system is a technology used to process data, including processing, obtaining, compiling, storing, and manipulating data in various ways to produce quality information, namely information that is relevant, accurate, and timely, which is used in personal, business, and government purposes and is strategic information for decision making. Information systems with technological support are one of the systems that play a significant role in organizational success. The purpose of this study was to determine the success factors of the management information system (SIM-RS) at Hermina OPI Jakabaring Hospital based on the DeLone and McLean theory, which consists of six variables, namely system quality, information quality, service quality, use, user satisfaction and benefits. This research was conducted at Hermina OPI Jakabaring Hospital with a sample of 48 hospital employees who use SIM-RS. The results obtained from this study were based on the system quality variable, which stated that as many as 48% of employees stated SIM-RS quality. Information quality variables as much as 54% of respondents stated that SIM-RS was qualified. As many as 79% of respondents stated that they were satisfied with the service quality variable of SIM-RS. The use variable as many as 43% of respondents stated that SIM-RS was often used. As for the user satisfaction variable, as many as 94% of respondents stated that SIM-RS was of high quality. The benefit variable was that as many as 56% of respondents stated that SIM-RS was useful.